2014
DOI: 10.1007/s00705-014-2052-0
|View full text |Cite
|
Sign up to set email alerts
|

White spot syndrome virus (WSSV) infection in shrimp (Litopenaeus vannamei) exposed to low and high salinity

Abstract: White spot syndrome virus (WSSV) has a worldwide distribution and is considered one of the most pathogenic and devastating viruses to the shrimp industry. A few studies have explored the effect of WSSV on shrimp acclimated to low (5 practical salinity units [psu]) or high ([40 psu) salinity conditions. In this work, we analysed the physiological response of WSSV-infected Litopenaeus vannamei juveniles that were acclimated to different salinities (5, 15, 28, 34 and 54 psu). We evaluated the osmotic response and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…The physiological response of L. vannamei juveniles infected with white spot syndrome virus (WSSV) was evaluated at 5, 15, 28, 34 and 54 psu, respectively, and the susceptibility of the shrimp to the virus increased at extreme salinities (5 or 54 psu), with higher survival at the salinities of 15 or 28 psu close to the iso‐osmotic point of L. vannamei (Ramos‐Carreno et al . ). In another study, after shrimp were challenged with V. alginolyticus and WSSV after exposure to 2.5, 5, 15, 25 or 35 psu for 24 weeks, the animals were then removed to their respective salinities for recovery (Lin et al .…”
Section: Physiological Response Of Litopenaeus Vannamei To Low Salinitymentioning
confidence: 97%
“…The physiological response of L. vannamei juveniles infected with white spot syndrome virus (WSSV) was evaluated at 5, 15, 28, 34 and 54 psu, respectively, and the susceptibility of the shrimp to the virus increased at extreme salinities (5 or 54 psu), with higher survival at the salinities of 15 or 28 psu close to the iso‐osmotic point of L. vannamei (Ramos‐Carreno et al . ). In another study, after shrimp were challenged with V. alginolyticus and WSSV after exposure to 2.5, 5, 15, 25 or 35 psu for 24 weeks, the animals were then removed to their respective salinities for recovery (Lin et al .…”
Section: Physiological Response Of Litopenaeus Vannamei To Low Salinitymentioning
confidence: 97%
“…Despite the ability to adapt to a wide range of salinity, hypo‐ and hyperosmoregulation lead to greater stress and energy intake often resulting in adverse effects to shrimp survival, growth and feed efficiency (Bray, Lawrence, & Leung‐Trujillo, ; Ramos‐Carreño et al., ; Sui, Ma, & Deng, ). In order to mitigate the effects of extreme salinity on shrimp culture, various studies have been conducted on dietary manipulation (carbohydrate, Wang et al., ; minerals, Gong, Jiang, Lightner, Collins, & Brock, ; Roy, Davis, Saoud, & Henry, ; Roy, Davis, Nguyen, & Saoud, ; Zhou, Zhang, Liu, & Ding, ; amino acids, Liu et al., ; crude protein, Sui et al., ; fatty acids, González‐Félix, Perez‐Velazquez, Quintero‐Alvarez, & Davis, ; alternative protein sources, Roy, Bordinhon et al., ; cholesterol and lecithin, Gong et al., ; Roy, Davis, & Saoud, ) and pond management strategies (water ionic concentrations, Limhang, Limsuwan, Chuchird, & Taparhudee, ; feeding rates, Roy, Davis, & Whitis, ).…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by Rodríguez et al (2003) suggested an apparent association between lower temperature and increased shrimp mortality rates. Thus, given importance of this industry and the limitations of high-intensity cultivation due to viral infections causing high mortality (Ramos-Carreño et al, 2014;Melena et al, 2015), particularly in extreme salinities (50), the development of prevention methods against WSV and other viruses would be necessary (Witteveldt et al, 2004a(Witteveldt et al, , 2004b). …”
Section: ______________________mentioning
confidence: 99%